Installing Lights on Wishon Christmas Tree at 6th and Huntington Blvd. - Watkins, Howard::::::::: (1987)
Cherry picker extended to add decorations to tree; people and boxes of decorations nearby Lamp post with street signs in foreground; Wishon home in background